High-dose dual therapy for Helicobacter pylori eradication inducing less impact on the gut microbiota - Jia-Lun Guan; Ting-Ting Xu; Ya Lin; Yan-Shuai Mo; Bi-Yu He; Ying-Ying Han; Ji-Yan Li; Su-Hong Xia; Ya-Ni Zhou; Jia-Zhi Liao; Pei-Yuan Li (Gut Pathogens)
Abstract Background Helicobacter pylori (H. pylori) eradication regimens may have different effects on the gut microbiota. Few studies have analyzed the safety of high-dose dual therapy (HDDT) from a micro-ecological perspective. This study aimed to compare the impact of H. pylori eradication with HDDT and bismuth quadruple therapy (BQT) on gut microbiota. Patients and methods H. Pylori-infected treatment-naive patients were recruited and screened from September 2023 to April 2024 and randomly assigned to the HDDT group (esomeprazole 20 mg, amoxicillin 750 mg, qid, 14 days) or BQT group (esomeprazole 20 mg, amoxicillin 1000 mg, clarithromycin 500 mg, and bismuth potassium citrate 600 mg, bid, 14 days). Fresh stool specimens were collected and stored before treatment and at week 2 and week 8 after treatment. The diversity and composition of the gut microbiota were compared and analyzed in both groups using 16 S rRNA gene sequencing. Results Forty-nine H. pylori positive patients were enrolled and randomly assigned to either the HDDT (n = 24) or the BQT group (n = 25) group. Compared with baseline, alpha and beta diversities significantly changed at week 2 after receiving BQT and did not recover fully at week 8. However, in the HDDT group, the diversities at week 2 changed mildly without statistical significance, compared to baseline. Additionally, a greater number of species had alterations in their abundances in the BQT group compared to the HDDT group at week 2. However, the abundances of these species were restored to their previous levels at week 8 in both the HDDT and BQT groups. Conclusions Compared to BQT, HDDT exerted less impact on the diversity and composition of the gut microbiota. Clinical trial registration ChiCTR2100053268.